Synthesis And Characterisation Of N-Doped Graphene Quantum Dots/Titanium Dioxide Nanocomposite As Photosensitiser In Photodynamic Therapy For Breast Cancer Treatment - Ramachandran, Pravena (2021)
Titanium dioxide nanoparticles (TiO2 NPs) have been proven to be a potential candidate in cancer therapy, particularly in the application of photodynamic therapy (PDT). However, the application of TiO2 NPs is limited due to the fast recombination rate of electron (e-)/hole (h+) pairs attributed to their wider bandgap energy. Thus, surface modification is explored to shift the absorption edge to a longer light wavelength to allow penetration into deep-seated tumours. In this study, TiO2 NPs conjugated with N-doped graphene quantum dots composites (N-GQDs/TiO2 NCs) to extend the light absorption properties of TiO2 to longer near-infrared (NIR) wavelengths. A facile one-pot hydrothermal method was employed to synthesise N-GQDs with an average particle size of 4.40 ± 1.5 nm at optimum conditions with molar ratio citric acid (CA):ethylenediamine (EDA) (1:1) at 180 °C for 4 h and primary amine (EDA) as the N-precursors. The blue emissive N-GQDs have photoluminescence (PL) quantum yield of 80.2 %, exhibited excitation-independent PL emission at 442 nm, with an excitation wavelength of 340 nm. Whereas, the anatase TiO2 NPs were synthesised using microwave-assisted synthesis in the aqueous phase with an average particle size of 11.46 ± 2.8 nm, a small crystallite size (12.2 nm) and low bandgap energy (2.93 eV).